Advanced bone age as an indicator facilitates the diagnosis of precocious puberty - Xu,Yue-Qin (2018)
Abstract Objective: Diagnosis of central precocious puberty has always been challenging in clinical practice. As an important method in the diagnosis of central precocious puberty, luteinizing hormone-releasing hormone stimulation test is complex and time-consuming. In many cases, clinical traits are inconsistent with luteinizing hormone-releasing hormone stimulation test results, therefore not reliable for diagnosis. In this study, the authors intended to find an indicator that predicts the results of the luteinizing hormone-releasing hormone stimulation test among subjects with early pubertal signs. Methods: Cases of 382 girls with early breast development before 8 years old and luteinizing hormone-releasing hormone stimulation test before 9 years old were included and underwent follow-up tests. Patients with peak luteinizing hormone level ≥5 IU/L were considered positive in the luteinizing hormone-releasing hormone stimulation test. Anthropometric data, body mass index, bone age evaluation, blood hormones levels of luteinizing hormone, estradiol, follicle-stimulating hormone, and uterine and ovarian volumes were analyzed. Results: Subjects with positive results in the initial test demonstrated early bone maturation, accelerated growth, and elevated basal blood luteinizing hormone, estradiol, and follicle-stimulating hormone levels, when compared with subjects with negative results in the initial test. Subjects with positive results in the follow-up test presented a more advanced bone age and more accelerated linear growth, when compared with subjects with negative results in the follow-up test. Conclusions: According to the statistical analysis, advanced bone age is the most effective predictor of the result of luteinizing hormone-releasing hormone stimulation test.